O amanhã de quem cresce: influências e valores presentes na constituição de projetos de vida de jovens adolescentes de um curso técnico de uma instituição estadual - Mattielo Junior, Gilberto Luiz [UNESP] (2015)
The changes that the young faces in adolescence are diverse, both physical and psychological, and directly influence the choices they must make because of their increasing integration into society. The responsibility and pressure to make decisions, largely imposed by the environment, will be factors that will mark the formation of their identity. Thus, the young create and adapt their life project according to their values and reactions when face internal influences - body changes, the faced mourning, etc. - and external ones - family, friends, media, school, among others. This research, based on their main objective of investigating the relationship between life project, values and internal and external influences of students from a state technical course, has quantitative and qualitative, descriptive and exploratory feature. It ranks as bibliographic and case study regarding the methodological procedures. Thereby, it carried out exploratory research involving documentary survey of statistical sources and data from Brazilian and American research about the young's profile, their purpose and the cultural influences that permeate them, and literature survey for the theoretical constitution. The executed case study in turn occurred with 12 young teenagers - aged 18 years old or more - in an Integrated to High School Administration Technical Course class of a Paraná state institution by a semi-structured interview (Stanford Protocol) based on the questionnaire of the human development psychologist William Damon, application of the instrument developed by Gouveia known as Basic Value Survey (BVS), and the questionnaire for personal and economic characterization of the participants (Critério Brasil). The results showed that the family is one of the most outstanding aspects in the students' life and that most influence them; the values they consider the most important to themselves - success, social support, religious, obedience...